2018
DOI: 10.1186/s13550-018-0452-y
|View full text |Cite
|
Sign up to set email alerts
|

In vivo confirmation of altered hepatic glucose metabolism in patients with liver fibrosis/cirrhosis by 18F-FDG PET/CT

Abstract: ObjectiveThe aim of this study was to assess the value of 18F-FDG PET/CT for quantitative assessment of hepatic metabolism in patients with different stages of liver fibrosis/cirrhosis.Materials and methods18F-FDG PET/CT scans of 37 patients either with or without liver fibrosis/cirrhosis, classified according to the METAVIR score (F0-F4) obtained from histopathological analysis of liver specimen, were analyzed retrospectively and classified as follows: no liver fibrosis (F0, n = 6), mild liver fibrosis (F1, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 71 publications
(56 reference statements)
1
16
0
Order By: Relevance
“…In patients with NASH, the [ 18 F]FDG assessed using the SUV analysis showed little promise [ 23 ]. Nevertheless, the increased [ 18 F]FDG update in liver fibrosis observed in this study is in general agreement with the findings of the human study reported by Verloh et al [ 24 ] and the animal study reported by Su et al [ 25 ]. With BDL, GLUT-1 levels quantified by IHC demonstrated increased expression in this study ( Figure 5 ).…”
Section: Discussionsupporting
confidence: 94%
“…In patients with NASH, the [ 18 F]FDG assessed using the SUV analysis showed little promise [ 23 ]. Nevertheless, the increased [ 18 F]FDG update in liver fibrosis observed in this study is in general agreement with the findings of the human study reported by Verloh et al [ 24 ] and the animal study reported by Su et al [ 25 ]. With BDL, GLUT-1 levels quantified by IHC demonstrated increased expression in this study ( Figure 5 ).…”
Section: Discussionsupporting
confidence: 94%
“…3c–g ). Because glucose metabolism provides a reliable measure of liver inflammation 34 , we were able to further rule out liver inflammation prior to therapy as a predisposing cause of CD4 + T EM ≥21% hepatitis by estimating hepatic glucose uptake in patients who underwent 18 F-fluoro-2-deoxy- d -glucose ( 18 F-FDG) PET/CT studies as part of routine tumour staging shortly before starting immunotherapy (Fig. 3h ).…”
Section: Resultsmentioning
confidence: 99%
“…Hepatic glucose metabolism as a measure of liver inflammation 34 was analysed retrospectively in all 32 patients who underwent pretreatment 18 F-FDG positron emission tomography and computed tomography (PET-CT) imaging as part of routine tumour staging shortly before starting immunotherapy. After overnight fasting, whole-body PET acquisitions covering at least the trunk were started 60–90 min after i.v.…”
Section: Methodsmentioning
confidence: 99%
“…Although glucose levels in the blood of cirrhotic rats and humans in the postprandial period do not differ from the norm ( Table 1 and Table 2 ), the metabolism of glucose in the case of LC undergoes significant changes [ 8 , 31 , 32 , 33 ]. An important indicator of the state of glucose metabolism in the liver is the content of glycogen, the level of which depends on the rates of its synthesis and degradation.…”
Section: Discussionmentioning
confidence: 99%